2013
DOI: 10.1093/molehr/gat053
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP efflux, via MRPs and A1 adenosine receptors, is critical for bovine sperm capacitation

Abstract: Sperm capacitation has been largely associated with an increase in cAMP, although its relevance in the underlying mechanisms of this maturation process remains elusive. Increasing evidence shows that the extrusion of cAMP through multidrug resistance associated protein 4 (MRP4) regulates cell homeostasis not only in physiological but also in pathophysiological situations and studies from our laboratory strongly support this assumption. In the present work we sought to establish the role of cAMP efflux in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 52 publications
2
29
0
1
Order By: Relevance
“…Interestingly, these initial high cAMP levels are rapidly reduced 43 for human sperm,44 for boar sperm . Decrease of cAMP levels could be attributed either to hydrolysis by phosphodiesterases (see below) or to cAMP extrusion by specific transporters 45 . As expected, the increase in cAMP immediately activates PKA activity 44 .…”
Section: Role Of Camp In Sperm Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these initial high cAMP levels are rapidly reduced 43 for human sperm,44 for boar sperm . Decrease of cAMP levels could be attributed either to hydrolysis by phosphodiesterases (see below) or to cAMP extrusion by specific transporters 45 . As expected, the increase in cAMP immediately activates PKA activity 44 .…”
Section: Role Of Camp In Sperm Functionmentioning
confidence: 99%
“…Interestingly, the expression of members of the multidrug resistance-associated proteins (MRPs) family has been reported in mammalian sperm 45 . MRPs, also members of the ATP binding cassette (ABC) transporter subfamily C, are known to actively transport cAMP and cGMP and other small non-structurally-related compounds to the extracellular environment One member of this family, MRP4 is localized to the sperm flagellum and to the post acrosomal region of bovine sperm 45 . In addition, this work showed that cAMP is extruded to the extracellular milieu and that MRP inhibition by probenecid abolished this efflux resulting in the accumulation of intracellular cAMP.…”
Section: Camp-dependent Signalling Pathwaysmentioning
confidence: 99%
“…Quite a few works deal with identification of adenosine receptors (AdenR) and elucidation of their role in control of fertility of spermatozoa [50][51][52][53][54]. It is shown by immunocytochemical methods that AdenR of the 1st (Aden 1 R) and 2nd types (Aden 2 R) that by the accordingly inhibiting and excitating way are coupled to AC, are present in the acrosomal area and in flagella, particularly in the main part of flagella enriched in microtubules.…”
Section: Identification In Spermatozoa Of Receptors Coupled To G-protmentioning
confidence: 99%
“…This agrees with the key role of Aden 1 R in regulation of late capacitation, chemotaxis, and acrosomal reaction, which is necessary for penetration of spermatozoon into the oocyte. In this aspect, of interest seems the point of view expressed by the Argentinian researchers in 2013 about that activation of Aden 1 R at late stages of capacitation is necessary for a decrease of the cAMP level that prior to this was increased due to stimulation of tmAC by hormones and sAC by bicarbonateanions [54]. This decrease is achieved both due to inhibition of the tmAC activity via G i -proteins and owing to the mediated Aden 1 R activation of MRP4 (multidrug resistance associated protein 4), a highly affine transporter for cAMP that at the stage of capacitation colocalizes with Aden 1 R in the anterior part of the spermatozoan head and performs release of cAMP into extracellular space.…”
Section: Identification In Spermatozoa Of Receptors Coupled To G-protmentioning
confidence: 99%
See 1 more Smart Citation